2020
DOI: 10.1021/acs.est.9b04500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Earthworms on the Microbiomes and Antibiotic Resistomes of Detritus Fauna and Phyllospheres

Abstract: Our understanding of the influences of animals on microbial communities and antibiotic resistance genes (ARGs) throughout the food web is limited, particularly in the soil ecosystem. We performed a microcosm experiment using the combination of 16S rRNA gene high-throughput sequencing and highthroughput qPCR to study the effects of earthworms on the microbiomes and resistomes of the phyllospheres and soil detritus fauna. A full factorial design was employed in this study, including two earthworm treatments (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…We observed that all unique microbial taxa belong to Verrucomicrobia were exclusively found in nematodes, all unique microbial taxa belong to Bacteroidetes were only determined in nematodes, oribatid mites, and predatory mites, most of unique microbial taxa belong to Actinobacteria and Tenericutes were exclusively observed in oribatid mites and predatory mites, and many unique microbial taxa belong to Proteobacteria were only detected in nematodes, potworms, oribatid mites, and predatory mites. Some of these abundant and unique bacterial taxa were also reported in previous studies [ 12 15 , 19 ]. A collection of unassigned taxa with no genome representatives were exclusively found in potworms, oribatid mites, and predatory mites, which were highlighted by red dots in Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…We observed that all unique microbial taxa belong to Verrucomicrobia were exclusively found in nematodes, all unique microbial taxa belong to Bacteroidetes were only determined in nematodes, oribatid mites, and predatory mites, most of unique microbial taxa belong to Actinobacteria and Tenericutes were exclusively observed in oribatid mites and predatory mites, and many unique microbial taxa belong to Proteobacteria were only detected in nematodes, potworms, oribatid mites, and predatory mites. Some of these abundant and unique bacterial taxa were also reported in previous studies [ 12 15 , 19 ]. A collection of unassigned taxa with no genome representatives were exclusively found in potworms, oribatid mites, and predatory mites, which were highlighted by red dots in Fig.…”
Section: Resultssupporting
confidence: 77%
“…These animal extinctions might hide a deeper crisis, involving the potential loss of thousands of unique microbial species living within the microbiome of these soil fauna (Scenarios 1 and 2; Fig. S1 ), because recent studies have shown that diverse microbial communities inhabit soil fauna [ 12 15 ]. The impact of invertebrate extinctions would not be as severe for microorganisms if different soil invertebrates shared similar microbiomes (Scenario 3; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA samples were first dispensed, then the mixtures of primers and fluorescence (in 384-well plates) using the Multisample Nanodispenser. The cycling conditions were set according to previous studies 22, 28, 29 and shown as follows: 10 min denaturation at 95°C, 40 cycles with 30 s amplification at 95°C and 30 s final extension at 60°C. The amplification efficiencies within 1.8 to 2.2 were considered as positive results.…”
Section: Methodsmentioning
confidence: 99%
“…The amplification efficiencies within 1.8 to 2.2 were considered as positive results. Threshold of 31 cycles (C t ) was set to be detection limit 29 . Three replicates were conducted for each sample.…”
Section: Methodsmentioning
confidence: 99%